High-Intensity Functional Training (HIFT): Definition and Research Implications for Improved Fitness - Yuri Feito; Katie M. Heinrich; Scotty J. Butcher; Walker S. Carlos Poston (MDPI AG, 2018)
High-intensity functional training (HIFT) is an exercise modality that emphasizes functional, multi-joint movements that can be modified to any fitness level and elicit greater muscle recruitment than more traditional exercise. As a relatively new training modality, HIFT is often compared to high-intensity interval training (HIIT), yet the two are distinct. HIIT exercise is characterized by relatively short bursts of repeated vigorous activity, interspersed by periods of rest or low-intensity exercise for recovery, while HIFT utilizes constantly varied functional exercises and various activity durations that may or may not incorporate rest. Over the last decade, studies evaluating the effectiveness of HIIT programs have documented improvements in metabolic and cardiorespiratory adaptations; however, less is known about the effects of HIFT. The purpose of this manuscript is to provide a working definition of HIFT and review the available literature regarding its use to improve metabolic and cardiorespiratory adaptations in strength and conditioning programs among various populations. Additionally, we aim to create a definition that is used in future publications to evaluate more effectively the future impact of this type of training on health and fitness outcomes.